Relational-cultural therapy - Jordan, Judith V. (Theories of psychotherapy series., 2018)
"In this second edition of Relational-Cultural Therapy, Judith V. Jordan returns to explore the history, theory, and practice of relationship centered, culturally oriented psychotherapy. Western psychological theories generally depict human development as moving from dependence to independence. In contrast, relational-cultural therapy is built on the premise that, throughout the lifespan, human beings grow through and toward connection, and that we need connections to flourish. This theory views isolation, at both individual and cultural levels, as a major source of suffering. The goal of the relational therapist is to deepen the therapeutic relationship and, ultimately, the client's relationships outside of therapy. The client's relational images -- positive or negative expectations created by past relationships -- influence current relationships, and a negative image can result in disconnections between people and society. This essential primer, amply illustrated with case examples, is perfect for graduate students and seasoned practitioners alike. This new edition highlights new research on the effectiveness of relational-cultural therapy in a variety of real-world situations -- such as developing team-building exercises in workplaces, and providing a theoretical frame for an E.U.-sponsored conference on human trafficking."--Preface. (PsycINFO Database Record (c) 2017 APA, all rights reserved)